VD_FINDINFO Jug / 2011 / 174 vom 5. Mai 2011 - VD Tribunal cantonal (2011)
ESCROQUERIE EN MATIÈRE DE PRESTATIONS, SÉJOUR ILLÉGAL, TRAVAIL AU NOIR | 146 al. 2 CP, 2 al. 2 CP, 2 CP, 23 al. 1 LSEE, 23 LSEE